2015
DOI: 10.1002/pro.2632
|View full text |Cite
|
Sign up to set email alerts
|

Structure, activity, and stability of metagenome‐derived glycoside hydrolase family 9 endoglucanase with an N‐terminal Ig‐like domain

Abstract: A metagenome-derived glycoside hydrolase family 9 enzyme with an N-terminal immunoglobulin-like (Ig-like) domain, leaf-branch compost (LC)-CelG, was characterized and its crystal structure was determined. LC-CelG did not hydrolyze p-nitrophenyl cellobioside but hydrolyzed CMcellulose, indicating that it is endoglucanase. LC-CelG exhibited the highest activity at 70 C and >80% of the maximal activity at a broad pH range of 5-9. Its denaturation temperature was 81.4 C, indicating that LC-CelG is a thermostable e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 31 publications
1
21
0
Order By: Relevance
“…Previous reports confirmed that structures of the catalytic domains of GH family 9 enzymes are characterized by an (␣/␣) 6 -barrel fold with three acidic active-site residues (two aspartate residues and one glutamate residue) (18). The C terminus-free MiXen showed highest identity scores with three characterized GH9 enzymes, including GH9 endoglucanase LC-CelG from an uncultured bacterium (accession number AHL27900, 24% identity), cellobiohydrolase CbhA from Clostridium thermocellum (PDB entry 1RQ5, 21% identity), and endoglucanase AaCel9A from Alicyclobacillus acidocaldarius (acces-sion number ACV59481, 19% identity).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Previous reports confirmed that structures of the catalytic domains of GH family 9 enzymes are characterized by an (␣/␣) 6 -barrel fold with three acidic active-site residues (two aspartate residues and one glutamate residue) (18). The C terminus-free MiXen showed highest identity scores with three characterized GH9 enzymes, including GH9 endoglucanase LC-CelG from an uncultured bacterium (accession number AHL27900, 24% identity), cellobiohydrolase CbhA from Clostridium thermocellum (PDB entry 1RQ5, 21% identity), and endoglucanase AaCel9A from Alicyclobacillus acidocaldarius (acces-sion number ACV59481, 19% identity).…”
Section: Resultsmentioning
confidence: 59%
“…The molecular mass distributions of xanthan digests produced by excessive amounts of enzymes were also detected by gel permeation chromatography (GPC) ( MiXen exhibits endotype xanthanase activity. MiXen resembles (24% sequence identity) the catalytic part of a GH9 from uncultured bacterium (PDB entry 3X17), which has been shown to be an endotype glucanase that exerts significant activities against CMC but no activity toward p-nitrophenyl cellobioside (18). Gel permeation chromatography analysis also provided information about the xanthan-degrading pattern of MiXen with time ( Fig.…”
Section: Resultsmentioning
confidence: 96%
“…The Ig-like domain was initially characterized as a structure composed of two sheets of antiparallel β strands [59]. Okano et al reported that the Ig-like domain contributed to the maintenance of the structure, activity and stability of metagenome-derived glycoside hydrolase family 9 endoglucanase [60]. Interestingly, the Ig-like domain made endoglucanase Cel9A from Alicyclobacillus acidocaldarius dependent on calcium [61].…”
Section: Discussionmentioning
confidence: 99%
“…Five glycosidases from the GH3 (PDB 3U48 and 5K6M), GH9 (PDB 1JS4 and 3X17), and GH116 (PDB 5BX5) families that shared the highest similarity to Bgl1D were selected for the alignment (Table S5). Blast results showed that Bgl1D shared approximately 16.57%, 27.49%, 24.56%, 20.78%, and 26.67% identities with the amino acids of 3U48, 5K6M [39], 1JS4 [40], 3X17 [41], and 5BX5 [42], respectively. A comparison of the amino acid of Bgl1D with these β-glucosidases demonstrated that the Asp44 of Bgl1D was similar to 3U48 (GH3 family) and 1JS4 (GH9 family) whose residue Asp was generally used as conserved catalytic nucleophile base or catalytic proton donor according to the information of β-glucosidase (EC 3.2.1.21) from the CAZy database (http://www.cazy.org) ( Figure 3) [43].…”
Section: Discussionmentioning
confidence: 99%